Analisis Pendapatan Asli Daerah (PAD) Sebagai Upaya Menuju Kemandirian Daerah Provinsi Sulawesi Tengah - Rhena Maharani; Adfiyani Fadjar; Erwa Sastrawan (Manajemen Kreatif Jurnal, 2023)
The local government has attempted to implement regional autonomy, which has carried out development for 5 years through Regional Original Revenue (PAD) funding. The purpose of this research is to analyze the potential growth rate, as well as forecast the resource's future earnings. This study uses secondary data for the 2017-2021 financial and regional asset management bodies in Central Sulawesi with descriptive analysis. This research technique uses contribution ratio analysis techniques, growth ratios and trend ratios. These results indicate that the contribution of PAD sources found that local taxes and other legitimate PAD are the largest contributors to PAD in Central Sulawesi while levies and business entities still contribute and the elasticity is small, while the growth rate of PAD sources will have a tendency. of fluctuating growth rates.